Elecroantennogram Responses of the Cherry Fruit Fly Rhαgoletis cerαsi (Diptera: Tephritidae) to Naturally Occurring Volatiles - Raptopoulos, D.; Koutsaftikis, A.; Haniotakis, G.; Douma, E. (ENTOMOLOGIA HELLENICA, 1998)
EAG responses of the cherry fruit fly, Rhagoletis cerasi (Linne) (Diptera: Tephritidae) were recorded in response to seventy-eight generally occurring plant volatiles and male cherry fruit fly volatiles. The test compounds are representatives of three major classes of organic compounds, aldehydes, ketones, and monoterpenes. No differences were observed in the degree of response between males and females, Carbon-chain length, unsaturation, and position of functional groups all have significant effect on the magnitude of EAG response.